Legal Certainty in the Renewal of Mudharabah Contracts: An Analysis from the Perspective of DSN-MUI Fatwa - Hidayat Darussalam; Ava Martin (Journal of Nusantara Economy, 2025)
The dynamic nature of muamalah allows for legal adaptation and development (mutaghayyirāt) in response to contemporary economic realities. One of the contracts that has undergone significant ijtihād-based development is the mudharabah contract. In its classical conception, mudharabah is founded on trust (amanah) between the capital provider (shahib al-māl) and the entrepreneur (mudhârib), without requiring collateral as an essential element of the agreement. However, the growing complexity of modern Islamic financial institutions has led to the introduction of collateral requirements in mudharabah financing as a risk mitigation mechanism. This practice has generated scholarly debate regarding its compatibility with the original principles of mudharabah. As the authoritative body responsible for issuing collective legal opinions (fatwa jama'i) in Indonesia, the Indonesian Council of Ulama (Majelis Ulama Indonesia—MUI), through the National Sharia Council (DSN-MUI), plays a strategic role in guiding the development of Islamic economics, finance, and business. The DSN-MUI Fatwa concerning mudharabah financing provides legal justification for the use of collateral under specific circumstances, reflecting an adaptive form of contemporary Islamic legal reasoning. This study employs a normative legal research method with a library-based approach. It aims to analyze the renewal of the mudharabah contract through the ijtihād embodied in the DSN-MUI Fatwa on collateral in mudharabah financing and to examine its conformity with the objectives of Islamic law (maqāṣid al-sharī‘ah). The findings indicate that the inclusion of collateral in mudharabah contracts emerges from the need of Islamic financial institutions to safeguard entrusted funds, minimize moral hazard, and ensure contractual compliance. From the perspective of maqāṣid al-sharī‘ah, the collateral requirement can be justified as an instrument for protecting wealth (ḥifẓ al-māl) and promoting legal certainty, provided that it does not alter the fundamental nature of mudharabah as a profit-and-loss sharing contract. This study contributes to the contemporary discourse on Islamic contract law by demonstrating how collective ijtihād can reconcile classical fiqh principles with modern financial governance needs. Furthermore, it enriches the theoretical discussion on the flexibility of Islamic commercial law and provides a maqāṣid-based framework for evaluating contractual innovations in Islamic finance.